25. SLEEP QUALITY AMONG MEDICAL STUDENTS AT UNIVERSITY OF MEDICINE AND PHARMACY - VIETNAM NATIONAL UNIVERSITY STUDIED AT HOA LAC IN 2022-2023 (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the status of sleep quality of medical student at University of Medicine andPharmacy – Vietnam National University studied at Hoa Lac in 2022-2023.Subject and method: A cross - sectional study was carried out among 422 students on the first year inUniversity of Medicine and Pharmacy - Vietnam National University studied at Hoa Lac in 2022-2023.Results: The percentage of poor sleep quality according to the PSQI scale accounted for 36,5%(PSQI > 5).Conclusion: Sleep quality of medical students are not good, there should be improvements instudents’ knowledge about the importance of sleep as well as sharing from families and universitiesto reduce studying and social pressure among students.
Keywords: Sleep quality, PSQI, students.